2014
DOI: 10.1208/s12249-014-0193-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of siRNA Lipoplexes: Effect of Different Lipids, In Vitro Evaluation in Cancerous Cell Lines and In Vivo Toxicity Study

Abstract: Cationic liposomes have long been used as non-viral vectors for small interfering RNA (siRNA) delivery but are associated with high toxicity, less transfection efficiency, and in vivo instability. In this investigation, we have developed siRNA targeted to RRM1 that is responsible for development of resistance to gemcitabine in cancer cells. Effect of different lipid compositions has been evaluated on formation of stable and less toxic lipoplexes. Optimized cationic lipoplex (D2CH) system was comprised of diole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Although commercial transfection reagents Lipofectamine 2000 with VEGF shRNA exhibited a higher VEGF downregulation effect, apparent cytotoxicity could be caused by Lipofectamine 2000 at relatively high dosages, consistent with previous reports. 66 The expression of VEGF at the protein level was further measured by ELISA as shown in Figure 11B and was similar to the results obtained by qPCR. PLGA/PPF/VEGF shRNA showed a knockdown of VEGF expression (3,765 pg/mL) in comparison with the control (4,236 pg/mL) and PLGA/PPF/SC shRNA (4,411 pg/mL) groups.…”
Section: Vegf Gene Silencing Efficiency In Vitrosupporting
confidence: 75%
“…Although commercial transfection reagents Lipofectamine 2000 with VEGF shRNA exhibited a higher VEGF downregulation effect, apparent cytotoxicity could be caused by Lipofectamine 2000 at relatively high dosages, consistent with previous reports. 66 The expression of VEGF at the protein level was further measured by ELISA as shown in Figure 11B and was similar to the results obtained by qPCR. PLGA/PPF/VEGF shRNA showed a knockdown of VEGF expression (3,765 pg/mL) in comparison with the control (4,236 pg/mL) and PLGA/PPF/SC shRNA (4,411 pg/mL) groups.…”
Section: Vegf Gene Silencing Efficiency In Vitrosupporting
confidence: 75%
“…D2CH lipoplexes showed high cellular uptake of 83.83 ± 1.01% in A549 cells and 67.07 ± 0.86% in HT1299 cells which was five to six fold higher than that obtained with naked siRNA. As well, at 5 nM concentration D2CH lipoplexes showed 27.15 ± 1.85% gene expression while naked siRNA has 83.50 ± 2.5% gene expression in A549 cells (similar values were obtained in H1299 cells) -results that emphasize siRNA carriers importance (Khatri et al, 2014).…”
Section: Sirna Deliverysupporting
confidence: 64%
“…14,26,36 Data have suggested that the disaccharides interact directly with the polar groups of the lipids to prevent particle fusion during freezing and can also prevent ice formation by increasing the glass transition temperature of the solution. 34,37 Overall, freezing the LNPs at -80°C could maintain their stability with the help of trehalose or sucrose; however, deep freezers are not always available, particularly during transport.…”
mentioning
confidence: 99%